How does quality of life (QOL) affect attractiveness of cities and internal migration in Turkey? - İsmet Selçuk Özer; Umut Türk (Economic Themes, 2023)
The management of internal flows can bring significant benefits to a country in balancing the opportunities between regions or cities. To tackle unequal access to opportunities, the factors that induce internal migration should be understood. This study examines a set of pull and push factors for internal migration by spatial econometric analysis and GIS applications. We find that when the accessibility of amenities increases, the city becomes more attractive and preferable for migrants. In addition, socioeconomic factors also play a significant role in the decision-making process of migrants. In this study, we used a panel dataset that includes socioeconomic and contextual data such as distances to the amenities for each Turkish city in the years between 2012 and 2021. The results show that, in Turkey, internal migration flows from the East to the West, where opportunities are better. Finally, the human capital level of migrants can cause a variety of thoughts about factors, and it can change the order of significance of the variables for people who have a different level of human capital such as education level. Based on the findings, the paper offers several policies suggestions for ensuring a balanced migration in Turkey.
Keywords: R00; R23; 330; internal migration; quality of life; attractiveness; mobility; amenities; multilevel model; LISA